The streptozotocin-high fat diet induced diabetic mouse model exhibits severe skin damage and alterations in local lipid mediators - Alberto Leguina-Ruzzi; Rina Ortiz; Victoria Velarde (Biomedical Journal, 2018)
Background: Type 2 diabetes (T2D) can go undiagnosed for years, leading to a stage where produces complications such as delayed skin wound healing. Animal models have been developed in the last decades to study the pathological progression in this disease. Streptozotocin (STZ), that has a selective pharmacological toxicity toward pancreatic β cells, in addition to high fat diet has been widely used to induce diabetes however no evidence has shown its effects on the skin integrity. Methods: Eighteen C57BL/6J male mice, were divided in 3 groups; the first was fed with chow diet and the second was kept on a high fat diet and the third injected with STZ intraperitoneal for 5 days consecutively before starting the diet protocol with high fat. Mice were maintained 5 weeks in total. Results: We show that animals treated with STZ-high fat diet exhibit skin injuries without significant alterations on basal insulin and triglycerides, compared to the control. The skin from these animals presents higher levels of oxidative stress, lower levels of adhesion proteins and alterations in lipid mediators, effects that are not produced by the high fat diet itself. Conclusion: Our results suggest that this in vivo model represents a relevant approach for studying skin damage induced by diabetes. Keywords: Diabetes, Streptozotocin, Lipid mediators, Skin damage, Epithelial integrity